(3eQBI Gdaghe TQM ebOeI GdYdhes - (3CHh GdaOG ESeGYjd Hf EHQGgje GdYdhjs
(3ChdgG (B:s
(3aCHJOCJ TQkMG Ydi ebOeI GdYdhe GdJj CfTCgG GdEjLj s
(3BNQgG (B:s
(3GfJgi GdTQM s
(3Vef eLehY , JQJjHgG (B: 2s
(3GSe GdeDda hGSe GdfGSN aj GdNGJeI eWehSGfs
(3cGf GdaQGZ ef JCdjag aj (B17 (3eMQe YGe (B932 (3g`s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdeNWhWGJ (B- (3UfYGA (B((3GdefWb(B) s
Keywords: (3eJaQbGJs